Value proposition as a framework for value co-creation in crowd-funding ecosystem - Quero-Gervilla, María José; Ventura-Fernández, Rafael; Kelleher, Carol (My University, 2015)
The present paper suggests that crowd-funding in the arts and cultural sector occurs within a complex service ecosystem, where six categories of value propositions frame eight value co-creation processes, namely through ideation, evaluation, design, testing, launch, financing and authorship. Managerial contributions include the development of a crowd-funding service ecosystem model for arts managers, which offers not only a method of financing or economic value, but which also offers opportunities for strengthening bonds with customers and other stakeholders. Our paper is innovative in that we integrate value propositions categories with the micro – meso and macro contexts and analyse the different kind of co-creation are framed in the crowdfunding context
Keywords: Empresas - Finanzas; Redes sociales; Service ecosystems; Networks; Crowdfunding; Value propositions; Value co-creation; Service dominant logic